Self regulation effect to critical reasoning skills at childs - Lestari, Ester Tri; Purnamasari, Iin; Sulianto, Joko (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study was conducted because researchers found problems in children's cognition where, after almost two years of online learning, students need to adapt to face-to-face learning. Therefore, in the current offline learning, children are expected to think logically and reason according to their abilities at their age with stimulation in the real world. This study aims to determine the effect of self-regulation on critical thinking skills and the relationship pattern between the two. This study used a mixed-method approach with a sequential exploratory design. The independent variable is self-regulation, and the dependent variable is critical reasoning ability. The results showed that there was an effect of self-regulation on critical reasoning ability based on the Wilcoxon Signed Rank Test with a significance value < 0.05, and self-regulation can be strengthened by children through collaborative activities and fostering critical reasoning as indicated by the skill of developing transcripts based on children's reasoning obtained based on observations and interviews. It can be concluded that based on the results of qualitative analysis, quantitative analysis results, and analysis of relevant research results, it can be interpreted that, in general, the results of qualitative and quantitative analysis, as well as literature review, deepen and strengthen each other, so that information is obtained that there is an effect of self-regulation on the achievement of critical reasoning skills significantly.